Issues Of Introduction Of E-University In The Context Of Rapid Development Of Digital Technologies - I.Ergashev (International Scientific and Current Research Conferences, 2021)
This article examines the issues of introduction of e-University in the context of rapid development of digital technologies, improvement and implementation of information systems and resources, organization of electronic interaction, formation of unified electronic registers and databases. The proposals have been made for the widespread introduction of e-University.